Aldosterone and the Heart: From Basic Research to Clinical Evidence - Catena, C.; Colussi, G.; Marzano, L.; Sechi, L. A. (Hormone and Metabolic Research, 2012)
Recent views suggest that long-term exposure to elevated aldosterone concentrations might result in cardiac, vascular, renal, and metabolic sequelae that occur independent of the blood pressure level. Indirect evidence of the untoward effects of aldosterone on the heart has been clearly established in clinical studies that have tested the effects of mineralocorticoid receptor antagonists in the treatment of systolic heart failure. As it has become clear in recent years, the interaction between aldosterone and the heart has to deal with additional actions of the hormone on specific cell types, cellular mechanisms, and molecules that are involved in regulation of tissue responses, leading to hypertrophy, remodeling, and fibrosis. The majority of these effects are mediated by activation of the mineralocorticoid receptors that are expressed in cardiomyocytes and cardiac fibroblasts, and mediate the genomic effects of the hormone. Evidence of interactions between aldosterone and the heart that occur independent of the renal effects of aldosterone, however, is not limited to the context of systolic heart failure and observations obtained in other disease states have led, together with findings of animal studies, to a better understanding of the potential benefits of aldosterone antagonists. In this narrative overview, we highlight the most recent findings that have been obtained in experimental animal models and in clinical conditions that include, in addition to systolic heart failure, primary aldosteronism, essential hypertension, diastolic heart failure, and arrhythmia.
Keywords: arrhythmia; atrial fibrillation; essential hypertension; heart failure; mineralocorticoid receptor antagonists; primary aldosteronism; spironolactone